2022
DOI: 10.1108/arj-06-2021-0165
|View full text |Cite
|
Sign up to set email alerts
|

Financial distress, earnings management and Big 4 auditors in emerging markets

Abstract: Purpose The purpose of this study is to examine the association between financial distress and accruals-based earnings management in emerging markets, and the role that auditors play in that association. Design/methodology/approach This study relies on a sample of 33,455 firm-year observations from 20 emerging markets, covering a large period of analysis of 20 years. A multivariate analysis is performed by considering the level of financial distress as the dependent variable, and the accruals-based earnings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
2
20
0
5
Order By: Relevance
“…Therefore, taking our results as a whole, we find an improvement in the quality of the information reported by firms in periods of marked political and economic instability. In this sense, although in general emerging economies are characterized by lower levels of enforcement, higher levels of volatility and greater informality – which generally encourage earnings management practices in these countries (Viana et al. , 2022a) – our results suggest a decrease in this opportunistic practice during periods of greater uncertainty and political and economic imbalances.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, taking our results as a whole, we find an improvement in the quality of the information reported by firms in periods of marked political and economic instability. In this sense, although in general emerging economies are characterized by lower levels of enforcement, higher levels of volatility and greater informality – which generally encourage earnings management practices in these countries (Viana et al. , 2022a) – our results suggest a decrease in this opportunistic practice during periods of greater uncertainty and political and economic imbalances.…”
Section: Resultsmentioning
confidence: 72%
“…Economic growth and political stability are profoundly interconnected and important factors for societies' welfare (Hussain, 2014). This matter seems even more relevant in emerging market countries (Viana et al. , 2022a, b), where investors face greater information asymmetry (Martins and Barros, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, research shows that larger auditors provide better quality audits (Becker et al. , 1998; DeAngelo, 1981; Lennox, 1999; Viana et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The model below is used to test the hypotheses of the study: High-quality auditors contribute to lessen earnings management and also affect the construction of firms' internal control (Becker et al, 1998). Viana et al (2022) found that while a firm's level of financial distress positively affects accrual-based earnings management, this effect is weaker for firms audited by a Big 4 audit firm. Therefore, a variable for the audit firm was included in the model expecting a negative effect on earnings management.…”
Section: Model Specificationmentioning
confidence: 99%